2016
DOI: 10.1177/1558689815581561
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Participant-Generated Image Methods in the Social Sciences

Abstract: The final, definitive version of this paper has been published in Journal of Mixed Methods Research, Vol. 10(4): 335-351, October 2016, DOI: https://doi.org/10.1177/1558689815581561, first published online 13 April 2015, published by SAGE Publishing. ?? The Author(s) 2015This article makes a systematic review of the use of participant-generated image methods in social science research. Such methods have a long history of application across the social sciences. Their development has, however, been uneven and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 38 publications
(63 reference statements)
0
47
0
9
Order By: Relevance
“…The present study analyses forest visitors' associations with deadwood based on the VEP approach with 125 forest visitors participating. Balomenou and Garrod (2016) assume a mean of 113.2 participants after comparing almost 300 studies where the method was applied. But generally, VEP data sets have, as an initially qualitative research method, typically rather small case numbers, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The present study analyses forest visitors' associations with deadwood based on the VEP approach with 125 forest visitors participating. Balomenou and Garrod (2016) assume a mean of 113.2 participants after comparing almost 300 studies where the method was applied. But generally, VEP data sets have, as an initially qualitative research method, typically rather small case numbers, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In VEP, participants are requested to take photographs of their own environments and to accompany these with a word-based complementary method to ensure participants convey the meanings they wish to convey to the research team. A number of techniques consisting of the same components have been used over the years (see Balomenou and Garrod, 2016), with Visitor-Employed Photography (Traweek, 1977), Resident-Employed Photography (Stedman et al, 2004), and Host-Employed Photography (Brickell, 2012), among others. As it seems that the first of the three words in the name of the technique described above identifies a destination user group, and for the sake of common understanding and ease of literature searches, the authors of this paper prefer the umbrella term Volunteer-Employed Photography as it captures the nature of the activity, it allows for more than one volunteer groups to share the same technique, as they do the spaces they occupy, and also shares an acronym with the original VEP: Visitor-Employed Photography.…”
Section: Reclaiming Photographs As Data In the Social Sciencesmentioning
confidence: 99%
“…These studies are precedents for a still-underused means of illustrating subjects' experiences in their natural state (Loeffler, 2004;MacKay and Couldwell, 2004;Garrod, 2008;Balomenou et al, 2017). A review of peer-reviewed and "grey" literature from the 1970s to 2014 by Balomenou and Garrod (2016) identified 35 different names used for closely similar techniques in nearly 300 studies using photographs captured by participants explicitly for research purposes in the social sciences. The same authors have identified 76 studies within the tourism literature specifically between 1972 and 2016 (Balomenou and Garrod, 2018).…”
Section: Reclaiming Photographs As Data In the Social Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dozens of terms for PP have been used in the literature over the years. A review by Balomenou and Garrod () found forty‐two terms used for this process since the 1970s. The term currently most popular is photovoice.…”
Section: Introductionmentioning
confidence: 99%